Phylogenetics and geography of speciation in New World Halichoeres wrasses - Wainwright, Peter C.; Santini, Francesco; Bellwood, David R.; Robertson, D. Ross; Rocha, Luiz A.; Alfaro, Michael E. (Molecular phylogenetics and evolution, 2018)
[Display omitted] •Monophyly of New World Halichoeres including Oxyjulis and Saggitalarva.•Atlantic Ocean is the ancestral area.•Five of 25 speciation events occurred across Isthmus of Panama.•Trans-Isthmian speciation events range in age from 20.8 to 4.8 Ma.•Three speciation events across the Orinoco/Amazon outflow. The New World Halichoeres comprises about 30 small to medium sized wrasse species that are prominent members of reef communities throughout the tropical Western Atlantic and Eastern Pacific. We conducted a phylogenetic analysis of this group and related lineages using new and previously published sequence data. We estimated divergence times, evaluated the monophyly of this group, their relationship to other labrids, as well as the time-course and geography of speciation. These analyses show that all members of New World Halichoeres form a monophyletic group that includes Oxyjulis and Sagittalarva. New World Halichoeres is one of numerous labrid groups that appear to have radiated rapidly about 32 Ma and form a large polytomy within the julidine wrasses. We reconstruct the tropical Western Atlantic to be the ancestral area of New World Halichoeres, with four invasions of the Eastern Pacific and one reversal from East Pacific to Western Atlantic. These five speciation events were spread across the history of the group, with none corresponding closely to the time of the closure of the Isthmus of Panama. Three speciation events within the Atlantic occurred across the Orinoco-Amazon outflow and within the Pacific, five involve splits between lineages that occupy coastal reef systems and offshore islands. Of eight sister species pairs, seven show complete allopatry and one is fully sympatric.